A General Software Architecture for Information Systems - Thomsen, Kristine Stougård (DAIMI Report Series, 1992)
A general software architecture for large and medium size information systems is presented. The architecture is a multi-level client-server architecture, where all dependencies on hardware and software platform are encapsulated into modules. The architecture provides a skeleton around which to grow an information system and is independent of the actual data model, functionality and user interface of the system. It supports division of labour during development, and it supports maintenance and portability of the resulting system. In all these respects, the architecture is superiar to the architecture obtained when using fourth generation languages. The architecture has been successfully used in several large projects during the last 6 years and practical experience shows that it provides a reusable starting point for future development projects.